French involvement and solidarity in South West France with the Spanish Republic in the Spanish Civil War (1936-1939) - Astington, Oliver (2010)
My postgraduate research project since August 2009 has focused on the ways in which solidarity and support were created and developed between people in the South West of France and the Second Republic in Spain. The first chapter of my thesis looks at how support for leftist politics and Republicanism in Spain was developed in the South West, a border region with close social, economic and political connections to Spain, especially following the establishment of the Second Spanish Republic in April 1931. The second chapter investigates how community groups, local French Front Populaire committees, Trade Unions and left-wing political parties worked to establish solidarity with the Spanish Republicans, within their local communities, ranging from the large cities such as Toulouse and Perpignan, down to localized actions in smaller sous-préfectures and communes. This chapter aims to demonstrate that support for the Republic took root across the South West and was developed due to the strong links to her Iberian neighbour discussed in chapter one. Chapter three examines how smaller government connected of regional functionaries falling under the aegis of pro-Republicans in the French government circumvented Non-Intervention laws and supported the Republic via partisan acts of assistance in crucial border posts and aerodromes in the South West. This chapter aims to demonstrate that despite the traditional narrative of the Spanish Civil War, which emphasises France’s adherence to the Non-Intervention agreement from August 1936, on a local level a plethora of actions in favour of the Republic were carried out. This research constitutes a significant step towards understanding international solidarity during the conflict beyond the major players such as the USSR and Mexico, countries which flouted the Non-Intervention agreement in favour of the Republic without any qualms. Finally chapter four looks at the volunteers from the South West to fight alongside the Republicans against the Spanish Nationalists backed by Hitler and Mussolini. The chapter will also illuminate the complex network of support services provided in the region to those wishing to enlist in the Republican army, underlining the important social contribution provided by pro-Republican elements within border communities in the South West.